Unified theory on preservation of conditionally non‐blocking switches by the two‐stage interconnection network. Issue 6 (1st November 2018) - Li, Shuo‐Yen Robert
Abstract : A central focus of switching theory is on non‐blocking properties of switches and their scalability. Several types of conditionally non‐blocking switches have been known to be preserved by the two‐stage interconnection network. The preservation of each type is by a separate theory. This study presents a coherent theory that yields an infinite family of preserved types, incorporating all known ones. Recursive two‐stage interconnection networks, including all banyan‐type networks, construct conditionally non‐blocking switches that are most compact in connecting every input to every output and rich in applications.